2020
DOI: 10.1016/s2665-9913(20)30033-3
|View full text |Cite
|
Sign up to set email alerts
|

Lessons for rituximab therapy in patients with rheumatoid arthritis

Abstract: B-cell depletion therapy is an effective option for RA treatment, but depletion is frequently incomplete (>0.0001x10 9 /L at week 2). Complete B-cell depletion (CD) after rituximab is associated with good clinical response (R) and this status (CD-R) leads to long-term maintenance of therapy. Low pretreatment plasmablasts, concomitant DMARDs, no smoking exposure, ACPA/RF+ and a low IFNsignature are predictive of CD-R. Half of the patients that achieve CD-R with rituximab eventually stop experiencing this outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 71 publications
0
21
0
Order By: Relevance
“…autoimmune conditions vs. lymphoma) also given the significant heterogeneity in treatment schedules, intensity of anti-CD20 administration and previous treatments history [ 28 , 29 ]. As an example, in patients with systemic autoimmune diseases Rituximab is usually administered as two 1000 mg flat doses given 2 weeks apart, while in thrombocytopenic purpura scheduling usually consists of four weekly infusions of rituximab at a dose of 375 mg/m 2 [ 30 – 32 ]. Moreover, corticosteroids and or/methotrexate can be concurrently administered [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…autoimmune conditions vs. lymphoma) also given the significant heterogeneity in treatment schedules, intensity of anti-CD20 administration and previous treatments history [ 28 , 29 ]. As an example, in patients with systemic autoimmune diseases Rituximab is usually administered as two 1000 mg flat doses given 2 weeks apart, while in thrombocytopenic purpura scheduling usually consists of four weekly infusions of rituximab at a dose of 375 mg/m 2 [ 30 – 32 ]. Moreover, corticosteroids and or/methotrexate can be concurrently administered [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…As an example, in patients with systemic autoimmune diseases Rituximab is usually administered as two 1000 mg flat doses given 2 weeks apart, while in thrombocytopenic purpura scheduling usually consists of four weekly infusions of rituximab at a dose of 375 mg/m 2 [ 30 – 32 ]. Moreover, corticosteroids and or/methotrexate can be concurrently administered [ 32 ]. In NHL, anti-CD20 antibodies are always dosed at 375 mg/m 2 and given, together with alkylators-containing chemotherapy, at a three-weekly frequence for six courses followed, in the case of indolent NHLs, by a maintenance phase of bi-monthly administrations for 2 years [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“… 62 , 63 Most patients with severe neutropenia recover quickly, and there is no evidence that the condition worsens with further treatment cycles. 64 The cause of LON has been poorly investigated and many theories have been formulated; the most credited hypotheses is that homeostasis of granulocytes may be disturbed by chemokine stromal-derived factor-1 interacting with B-lymphocyte recovery. 65 In the PPMS clinical trial with ocrelizumab, decreased neutrophil counts were transiently found in 13% of patients compared to 10% in placebo.…”
Section: Safety and Tolerability Datamentioning
confidence: 99%
“…[48] Rituximab is one of the main B cells targeting monoclonal antibody agents (mAB) frequently used in managing neuroinflammatory disorders by acting as anti-CD20 mAB. [49,50] The expression of CD20 molecule is associated with B cell maturation, rituximab works effectively by depleting pre-B and memory B cells. [50] The use of rituximab can be considered as one of the highest risk agents to be used in hindering COVID-19 pandemic infection due to its toxic and dangerous side effects with a recommendation on considering the delay of rituximab treatment initiation in managing COVID-19 neurological symptoms.…”
Section: The Impact Of Immunotherapies In Managing Neurological Manifmentioning
confidence: 99%